Double-blind study of dextroamphetamine versus caffeine augmentation for treatment-resistant obsessive-compulsive disorder - Koran, Lorrin M; Aboujaoude, Elias; Gamel, Nona N (The journal of clinical psychiatry, 2009)
Two small, double-blind, placebo-controlled, single-dose, crossover studies found dextroamphetamine (d-amphetamine) 30 mg clearly superior to placebo in relieving symptoms of obsessive-compulsive disorder (OCD). We conducted a 5-week, double-blind, caffeine-controlled study to test the hypothesis that d-amphetamine, added after an adequate selective serotonin reuptake inhibitor (SSRI) or serotonin-norepinephrine reuptake inhibitor (SNRI) trial, would be more effective than caffeine in reducing residual OCD symptoms of moderate or greater severity. Between August 2006 and February 2008, we enrolled adults with DSM-IV OCD and a Yale-Brown Obsessive Compulsive Scale (Y-BOCS) score of >or= 20 after >or= 12 weeks of adequate treatment with an SSRI or SNRI. Subjects were randomly assigned to double-blind d-amphetamine 30 mg/d or caffeine 300 mg/d added to their SSRI/SNRI and other medications. Responders (first week mean Y-BOCS score decrease of >or= 20%) entered the study's 4-week double-blind extension phase. We enrolled 24 subjects, 11 women and 13 men, with a mean (SD) age of 40 (13.2) years and mean baseline Y-BOCS scores of 26.5 (4.1) for the d-amphetamine group (n = 12) and 29.1 (4.0) for the caffeine group (n = 12). At the end of week 1, 6 of 12 d-amphetamine subjects (50%) and 7 of 12 caffeine subjects (58%) were responders. At week 5, the responders' mean Y-BOCS score decreases were, for the d-amphetamine group (last observation carried forward), 48% (range, 20%-80%); and, for the caffeine group, 55% (range, 27%-89%). Obsessive-compulsive disorder and depression improvement were independent. The double-blind remained intact. No subject discontinued the study due to side effects. Larger, double-blind, placebo-controlled trials of both d-amphetamine and caffeine augmentation are needed in OCD subjects inadequately responsive to adequate doses of an SSRI or SNRI. clinicaltrials.gov Identifier: NCT00363298.